Computation Design: Nanostructured Lipid Carrier Formula of Pinostrobin - Anita Puspa Widiyana (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Nano lipid carriers (NLC) function by increasing the solubility and oral bioavailability of hydrophobic drugs. This study was conducted to estimate the solubility of pinostrobin in various types of solid and liquid lipid carriers through computational design and to select the optimal NLC formula with the best candidate lipid carriers. Pinostrobin and all lipid carriers were determined for their interactions with the AutoDockTools program. The values of the free energy binding (ΔG), the inhibition constant (Ki), and the type of interaction visibility were recorded as a result of the molecular docking. The interaction type of visualization was determined by the BIOVIA Discovery Studio program. The results showed that apocarotenal was the best liquid lipid carrier with a ΔG value of -3.57 kcal/mol and a Ki value of 2.40 mM. Cetosteryl alcohol was the best carrier for solid lipids, with a ΔG value of -2.18 kcal/mol and a Ki value of 25.35 mM. Apocarotenal and cetostearyl alcohol as lipid carrier candidates for the NLC formula of pinostrobin.